Impact of COVID-19 pandemic on the occurrence and outcome of cardiogenic shock complicating acute myocardial infarction. (3rd October 2022) - Motovska, Z; Hlinomaz, O; Hromadka, M; Kala, P; Klechova, A; Precek, J; Kettner, J; Mrozek, J; Cervinka, J; Matejka, J; Zohor, A; Bis, J; et al.
Abstract: Background: The COVID-19 pandemic had influenced the patient's behavior and impacted the homeostasis to a pro-thrombotic niveau. Aim: The study aimed to follow the impact of COVID-19 on the incidence and prognosis of cardiogenic shock complicated initially acute myocardial infarction (CS-AMI). Methods: We used data entered into a large national all-comers registry of coronary intervention over five years. From 1/2016 to 12/2020, 50, 745 AMI patients were included, and 2, 822 (5.6%) initially had CS. Results: The incidence of CS-AMI was significantly higher in the COVID period (2020) than the mean incidence in 2016–2019 (5.5% vs 6%, p=0.032). The difference was caused by significant increase of CS in acute STEMI (7.6% vs. 8.7%, p=0.011); it was 7.1% in 2016, 7.8% (2017), 7.6% (2018), 7.8% (2019), and 8.7% (2020). The CS complicated 2.3% (2016), 2.7% (2017), 2.7% (2018), 2.8% (2019), and 2.8% (2020) of NSTEMI. The observed rise in CS-STEMI incidence each month during the pandemic compared to the average incidence in non-pandemic years correlated with the substantial increase in the number of COVID infected/hospitalized (Table 1). In these months, no changes in time delay to reperfusion layout were observed in CS-STEMI patients (Table 2). Except of less frequent history of previous PCI (13.9% and 8.2%, p<0.001), we found no significant differences in the followed CS-STEMI patient characteristics in 2016–2019 and 2020; men 72.7% and 75.4% (p=0.1), mean age (SD) 66.3 (12.3)yrs and 66.3 (12.2) yrs, Diabetes 20.9% and 19.1% (p=0.2), CKD 5.4% and 5.7% (p=0.4), previous CABG 4.5 and 4.2% (p=0.5), left main disease (14.3% and 16%, p=0.5), one vessel disease 24.9% and 32.1% (p=0.9), pre-PCI TIMI flow 0 64.4% and 66.2% (p=0.6), post-PCI TIMI flow 3 76.7% and 76.9%. The COVID pandemic didn't influence the proportions of pre-hospital resuscitated CS-AMI patients (57.5% and 58.7%, p=0.6) and those on mechanical ventilation (67.8% and 68.3%, p=0.8). The 30-day mortality trend of CS-AMI was 53.7% in 2016, 51.6% (2017), 49.7% (2018), 49.3% (2019), and 47.9% (2020). And in CS-STEMI it was 50.8%, 47.1%, 46.4%, 44.1%, and 45.3% (P2019 vs. 2020 =0.8), respectively. Conclusion: Data from a large national all-comer registry showed an increase in the proportion of patients admitted to hospitals with STEMI complicated by CS in the year of the COVID pandemic. The CS rise correlated with the increase in the COVID infected population. Factors other than the patient's cardiovascular risk profile or prolongation of a time delay to reperfusion influenced this trend. We suggest that the availability of health care and patient adherence may have affected the risks control. We did not observe any effect of the pandemic on CS-AMI mortality. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health of the Czech Republic